SCREENING BACTERIAL OF ENDOPHYTIC PRODUCING AMYLASE, LIPASE AND PROTEASE FROM LEAVES OF Macaranga hullettii King ex Hook.f. - Sherly Pricilia; Winni Astuti; Eva Marliana (Jurusan Kimia FMIPA UNMUL, 2018)
The objective of this study was to screening test of endophytic bacteria producing amylase, lipase and protease from leaves Macaranga hullettii King ex Hook.f. Endophytic bacteria isolation was performed on nutrient agar (NA) and 21 single colonies of endophytic bacteria were obtained. Endophytic bacteria that all of the endophytic bacteria positive producing enzym, 8 of the endophytic bacteria positive amylase, 7 of the endophytic bacteria positive lipase and 4 of the endophytic bacteria positive protease.